Seed germination and vigor of four Philippine rice varieties as influenced by hydropriming and storage at various durations - Ranmeechai, Nipada; Lacap, Angelyn T.; Tac-an, Marina Isabel A.; Bayogan, Emma Ruth V. (2022)
Rice seed germination and vigor are vital qualities to improve seedling growth and eventual yield. This study determined the effects of different hydropriming (0, 6, 12, or 18 h) and storage duration (0, 1, 2, and 3 mo) on the seed germination properties and seedling vigor of three irrigated varieties 'Angelica', 'Tubigan 14', 'Tubigan 24' and a rainfed variety. -Title page.
Includes bibliographical references.
Keywords: Germination -- Philippines; Rice -- Varieties -- Philippines